Recovery of Assets From Perpetrators of Corruption to Maximize Recovery of State Losses (Discourse Journal on Law and Society, 2025)
Legal certainty (rechtssicherheit) is a fundamental pillar of the rule of law, ensuring that legal provisions are clear, consistent, and predictable. In the Indonesian criminal justice system, the Public Prosecutor holds a central position as the Dominus Litis (the owner of the case), determining which cases proceed to court. However, the implementation of prosecutorial authority often leans towards rigid legal positivism, creating a paradox where procedural certainty is achieved at the expense of substantive justice. Disparities in prosecution demands for similar crimes often lead to public distrust and legal uncertainty for justice seekers. This study aims to analyze the challenges in maintaining legal certainty and proposes a strategy to enhance the prosecutor's role through the integration of Restorative Justice and professional discretion. The research employs a normative juridical method with statutory and conceptual approaches, analyzing Attorney General Regulation No. 15 of 2020. The study finds that enhancing legal certainty requires shifting the paradigm from "mechanical prosecution" to "discretionary prosecution" based on conscience. To achieve this, prosecutors must be equipped with high-level cognitive skills to interpret "certainty" not just as textual compliance, but as the consistent application of fairness.